Uso de petroplintita e solo gibbsítico para imobilização de arsênio em rejeito de mineração - Santos, Juliano Batista dos (2018)
Arsenic is a very toxic element, and can cause serious problems to natural resources and to human health. Thus, it is recommendable to use amendments to immobilize this element where its levels are high. The work aimed to test the adsorption potential of As by some natural amendments with high iron and aluminum oxide contents: ironstone, ironstone soil and gibbsitic soil, mixed with tailings collected from a gold mining operation, with arsenic contents of 348 mg Kg -1 . All materials, after drying, were passed through a 2 mm sieve. For the experiment, 3 replicates of each amendment were used in proportions of 100:1, 100:10 and 100:20 (tailing/amendment). After homogenization, the mixtures were incubated at field capacity at 25 ° C, receiving water daily for 2 months, so that the interaction of As with the oxides could occur. After this period, water soluble and Mehlich-I arsenic were extracted and determined. In the incubated tailings, water-soluble As was 2.94 mg L -1 , decreasing to 0.02 mg L -1 with gibbsitic soil in the proportion 100:20, and to 0.04 mg L -1 in the 100:10 ratio. At the 100:1 ratio, water-soluble As reduced to 1.92 mg L -1 , with the gibbsitic soil. Mehlich-I As in the incubated tailings was 5.96 mg L -1 , decreasing to 2.46 mg L -1 with the ironstone soil at a 100:20 ratio. At the 100:10 ratio, Mehlich-I As decreased to 3.32 mg L -1 , and at the 100:1 ratio, it decreased slightly to 5.05 mg L -1 . The results suggest a good potential for the use of low-cost, natural oxidic soil materials for the mitigation of arsenic risks in tailings deposits and other mine spoils.